An electronic textile embedded smart cementitious composite - Irfan, Muhammad S.; Ali, Muhammad A.; Khan, Kamran A.; Umer, Rehan; Kanellopoulos, Antonios; Abdul Samad, Yarjan (Engineering reports (Hoboken, N.J.), 2022)
Structural health monitoring (SHM) using self‐sensing cement‐based materials has been reported before, where nano‐fillers have been incorporated in cementitious matrices as functional sensing elements. A percolation threshold is always required in order for conductive nano‐fillers modified concrete to be useful for SHM. Nonetheless, the best pressure/strain sensitivity results achieved for any self‐sensing cementitious matrix are <0.01 MPa−1. In this work, we introduce for the first‐time novel partially reduced graphene oxide based electronic textile (e‐textile) embedded in plain and as well as in polymer‐binder‐modified cementitious matrix for SHM applications. These e‐textile embedded cementitious composites are independent of any percolation threshold due to the interconnected fabric inside the host matrix. The piezo‐resistive response was measured by applying direct and cyclic compressive loads (ranging from 0.10 to 3.90 MPa). A pressure sensitivity of 1.50 MPa−1 and an ultra‐high gauge factor of 2000 was obtained for the system of the self‐sensing cementitious structure with embedded e‐textiles. The sensitivity of this new system with embedded e‐textile is an order of magnitude higher than the state‐of‐the‐art nanoparticle based self‐sensing cementitious composites. The composites showed mechanical stability and functional durability over long‐term cyclic compression tests of 1000 cycles. Additionally, a two time‐constant model was used to validate the experimental results on decay response of the e‐textile embedded composites. We introduce novel reduced graphene oxide based electronic textile (e‐textile) embedded in cementitious matrix for structural health monitoring. The piezo‐resistive response was measured by applying direct and cyclic compressive loads (0.1 to 3.9 MPa). A pressure sensitivity of 1.5 MPa‐1 and an ultra‐high gauge factor of 2000 was obtained for the system of the self‐sensing cementitious structure with embedded e‐textiles. The sensitivity of this new system with embedded e‐textile is many orders of magnitude higher than nanoparticle based self‐sensing of cementitious composites.